The Insurance Industry in Mauritius - Vittas, Dimitri (World Bank, Washington, DC, 2014)
The insurance industry is relatively well developed. It makes extensive use of reinsurance facilities and is free from the pervasive premium, product, investment, and reinsurance controls that have bedeviled the insurance markets of so many developing countries around the world. Total premiums amounted in 2001 to 4.1 percent of GDP, while insurance company assets were equivalent to 18 percent of GDP. Life insurance, which has been favored by generous tax incentives and has also benefited from the growth of pension business and housing finance, represents 61 percent of total premiums. Nonlife business is also well organized. Large industrial and commercial risks are reinsured with top international companies, while motor insurance, which is the largest class of business with 45 percent of total nonlife premiums, does not suffer from high loss ratios or unduly long delays in settlement. Investment limits are generally sound and, with some small but important exceptions, effectively nonbinding. There is no minimum requirement for investment in government securities. Investment in overseas assets is limited to 25 percent of total assets, except for foreign life companies and general insurance business which are not allowed to invest in overseas assets. The insurance sector is highly concentrated. The three largest groups have 76 percent of total assets. Despite the high level of concentration, the insurance industry appears to be competitive, operating with high efficiency and re Despite the high level of concentration, the insurance industry appears to be competitive, operating with high efficiency and reasonable profitability. Large and medium-size companies have strong reserves, appropriate reinsurance arrangements, and good profitability. However, several of the smaller companies have weak financial ratios and suffer from long delays in settling claims. Insurance regulation and supervision is entrusted to the Financial Services Commission (FSC). The current regulatory framework has many strong elements, including reliance on solvency monitoring, prudent asset diversification, international accounting standards, and actuarial methods. But there are some important gaps in corporate governance, internal controls, and risk management. In addition, solvency ratios are below international standards and do not include modern risk-based capital requirements. These gaps are already being addressed in two new draft insurance bills which contain many highly modern provisions. Implementing regulations on solvency and actuarial standards need to be developed. Insurance supervision has been invigorated since the creation of the FSC, but further strengthening is required. It needs to emphasize risk management and internal controls, to develop an early warning system, and to establish clear procedures for early and effective intervention. The FSC should require actuaries to report on the reinvestment risk faced by insurance companies and their exposure to a large and persistent fall in interest rates.